An efficient method for generation of Knock-out human embryonic stem cells using CRISPR/Cas9 system - Bohaciakova D; Renzova T; Fedorova V; Barak M; Kunova Bosakova M; Hampl A; Cajanek L
Human embryonic stem cells (hESCs)represent promising tool to study functions of genes during development, to model diseases, and to even develop therapies when combined with gene editing techniques such as CRISPR/Cas9 system. However, the process of disruption of gene expression by generation of null alleles is often inefficient and tedious. To circumvent these limitations, we developed a simple and efficient protocol to permanently downregulate expression of gene of interest in hESCs using CRISPR/Cas9. We selected p53 for our proof of concept experiments. The methodology is based on series of hESC transfection, which leads to efficient downregulation of p53 expression even in polyclonal population (p53 Low cells), here proven by a loss of regulation of the expression of p53 target gene, microRNA miR-34a. We demonstrate that our approach achieves over 80 percent efficiency in generating hESC clonal sublines that do not express p53 protein. Importantly, we document by a set of functional experiments that such genetically modified hESC do retain typical stem cells characteristics. In summary, we provide a simple and robust protocol to efficiently target expression of gene of interest in hESCs that can be useful for laboratories aiming to employ gene editing in their hESC applications/protocols.
Keywords: STEM CELLS (HESCS)